Handover trigger time selection algorithm in heterogeneous wireless networks environment - Ji-lei YAN; Jian-dong LI; Lin-jing ZHAO (Tongxin xuebao)
The handover trigger time selection problem for mobile user in the heterogeneous networks environment was discussed.Firstly,theoretical analysis of the handover trigger time selection was presented and the constraint which the optimal handover trigger time should satisfy was obtained.Then,an algorithm was proposed to predict the optimal handover trigger time based on the estimation of handover delay and the prediction of received signal strength.Simulation results show that this algorithm can effectively reduce the packet loss ratio and the probability of handover failure.